Reducing Risk and Preventing Accidents at Level Crossings - Waters Craig (Global Railway, 2020)
Improving India's Rail Network with State-of-the-Art Technology, The Implications of Coronavirus on the Rail Sector, WESTbahn's CEO Outlines What it Takes to Maintain Their Fleet.